The common commercial policy of the European Community with special reference to the Uruguay Round and EC-Turkey Customs Union. - Kaya, Yonca (My University, 1995)
unknown
Keywords: AVRUPA TOPLULUĞU-TÜRKİYE; GÜMRÜK BİRLİĞİ-TÜRKİYE